SECTIONAL TITLE UNIT OWNERS’ LIABILITY FOR PAYMENT OF BODY CORPORATE’S DEBTS - Henk Delport (Obiter, 2022)
This note focuses on the scope and application of section 47(1) of the Sectional Titles Act 95 of 1986. The section must be viewed in the context of certain key provisions of the Act. These are discussed briefly. Attention is also given to the changes made to the section by the Sectional Titles Amendment Act 7 of 2005. It is argued that although the Amendment Act has absolved some unit owners from liability for payment of the body corporate’s debts, it has introduced an uncertainty as to whether owners can be held liable for body corporate debts incurred before they became members of the body corporate.